The generic symbolism of the scarf in Russian culture - Vairakh, Iuliia; Kazorina, Anna (Mongolian Journal of Arts and Culture, 2024)
The article explores the symbolism of the headscarf in the linguistic picture of the world, reveals the linguocultural nature of the headscarf in relation to parents, people, and homeland. The paper analyzes the symbolic connections of the macroconcept genus and the image of the headscarf as a national symbol with a multi-layered seme structure. The symbolic connections of the macroconcept gender and the image of the headscarf are manifested in the general structure of the imagery of the texts. The purpose of the study: to identify the symbolic meanings of the image of a scarf. Determination of the symbolic features of the macroconcept genus is carried out using a set of methods: conceptual, interpretive, descriptive. We analyze the symbolic plan of the image ‘handkerchief’ on the basis of the selected representatives of the macroconcept genus. Родовая символика платка в русской культуре Аннотация: В статье исследуется символика платка в языковой картине мира, раскрывается лингвокультурная природа платка по отношению к родителям, народу, родине. В работе осмыслены символические связи макроконцепта род и образа платка как национального символа, обладающего многослойностью семной структуры. Символические связи макроконцепта род и образа платка проявляются в общей структуре образности текстов. Цель исследования: выявить символические значения образа платка. Определение символических признаков макроконцепта род осуществляется с помощью комплекса методов: концептуального, интерпретативного, дескриптивного. Нами анализируется символический план образа-символа “платок” на основе выделенных репрезентантов макроконцепта род. Ключевые слова: языковая картина мира, макроконцепт, символ, образ, платок, род, родина, народ